Recent advances in metal-catalysed oxidation reactions - Aleena Raju; Subhiksha Jothish; Kokila Sakthivel; Shachi Mishra; R. J. Gana; Kotaro Kikushima; Toshifumi Dohi; Fateh V. Singh (Royal Society Open Science)
Oxidation reactions are vital tools in synthetic organic chemistry. Oxidation of organic species such as alcohols, phenols, aldehydes and ketones provides synthetically valuable organic compounds, especially synthetic intermediates for several biologically active compounds. Some of these synthetic intermediates have shown their synthetic utility in the total synthesis of natural products. Several classical and modern synthetic approaches have been used to achieve these oxidation reactions. In this review article, various oxidation reactions achieved by metal catalysis are highlighted.